Learning where the jobs are [career growth]. - Selinger, C.
This paper identifies several emerging technologies that promise career growth. These include digital rights management, display technologies, fingerprinting, organic electronics, alternative fuels and the hydrogen economy, and Wi-Fi. The paper also provides some useful tips on how to stay current on the latest industry developments and effectively manage a career in a fast-changing technology world.
Keywords: Wi-Fi.; Alternative fuels; Digital rights management; Display technologies; Fingerprinting; Hydrogen economy; Organic electronics